2010
DOI: 10.1016/j.pharmthera.2009.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Minding the calcium store: Ryanodine receptor activation as a convergent mechanism of PCB toxicity

Abstract: Chronic low level polychlorinated biphenyls (PCB) exposures remain a significant public health concern since results from epidemiological studies indicate PCB burden is associated with immune system dysfunction, cardiovascular disease, and impairment of the developing nervous system. Of these various adverse health effects, developmental neurotoxicity has emerged as a particularly vulnerable endpoint in PCB toxicity. Arguably the most pervasive biological effects of PCBs could be mediated by their ability to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
311
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(329 citation statements)
references
References 416 publications
8
311
0
Order By: Relevance
“…The present compounds will nevertheless be useful to silence RyR1, and probably other RyR isoforms, in a number of pathological conditions in which abnormal RyR1 channel activity is involved. These include skeletal and cardiac myopathies (60), neurodegenerative disorders (61,62), and environmentally triggered disorders (12). Our results suggest that MCa P-Thr 26 is capable of normalizing two important dysfunctional properties of RyR1: by decreasing the sensitivity of RyR1 to cytoplasmic Ca 2+ , allowing a decrease of spontaneous CICR (Fig.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The present compounds will nevertheless be useful to silence RyR1, and probably other RyR isoforms, in a number of pathological conditions in which abnormal RyR1 channel activity is involved. These include skeletal and cardiac myopathies (60), neurodegenerative disorders (61,62), and environmentally triggered disorders (12). Our results suggest that MCa P-Thr 26 is capable of normalizing two important dysfunctional properties of RyR1: by decreasing the sensitivity of RyR1 to cytoplasmic Ca 2+ , allowing a decrease of spontaneous CICR (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…It was first identified in skeletal muscles (10) but is also broadly expressed in many other tissues such as pre-and postsynaptic sites within neurons of the brain (11). RyR calcium channels regulate Ca 2+ release from intracellular stores, and therefore represent crucial players of a number of physiological and toxicological processes, from muscle contraction to gene expression (12). As a consequence, silencing of the gene encoding RyR1 is lethal at birth (13).…”
mentioning
confidence: 99%
“…A QSAR for PCB neurotoxicity (Pessah et al, 2005), based on data for 28 ortho-substituted PCBs, and building on earlier work (Nevalainen et al, 1994), revealed a relationship between electronic descriptors (E LUMO , E HOMO , the E LUMO −E HOMO gap, and molecular polarizability) and the binding affinity of PCBs to the aryl hydrocarbon (Ah) receptor. In particular, impairment of the developing nervous system by PCBs has been linked to their ability to alter the spatial and temporal fidelity of Ca2+ signalling in muscle and nerve cells through one or more receptor-mediated processes (Pessah et al, 2009). …”
Section: Neurotoxicitymentioning
confidence: 99%
“…Interestingly, also the SlC25A12 gene, which encodes for AGC1, encompasses genetic variants able to influence disease risk in autism (Palmieri et al, 2010). Genetic vulnerability at the ATP2B2 and SLC25A12 loci could be exacerbated by prenatal environmental exposure to PCBs, important endocrine disruptors also able to promote Ca 2+ entry from the extracellular space, and Ca 2+ release from the endoplasmic reticulum (Pessah et al, 2010). 3.…”
Section: Clinical Perspectives Of Developmental Neurotoxicitymentioning
confidence: 99%